Songkabala in al-'Urf Perspective on Pinisi Vesselbuilding in Coastal Sulawesi - Pabbajah, Mustaqim; Ashufah, Abdul Hayyaqdhan; Eitriya, Zehratul (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
Pinisi vessel are cherished local heritage found in South Sulawesi up to the present day. Therefore, this research provided a comprehensive portrayal of songkabala ritual and conducted an in-depth analysis in Bulukumba, Indonesia. In the broader sociological framework, the intricate interplay between the local Bulukumba culture and Islamic law was analyzed. To examine songkabala rituals, theories such as al-'urf, symbolic interactionism, and legal sociology were established. This method presented an understanding of qualitative research, using data sources gathered through systematic observation, insightful interviews, and meticulous documentation. Data analysis was conducted through the stages of selection, formatting, and conclusion. The results showed that songkabala was a ritual preserved for making pinisi vessels in Bulukumba tradition to ward off disasters faced when sailing. The ritual was performed with four stages, including annakbang, kalabiseang annattara, appasili, and ammossi. Based on al-'urf theory, songkabala activities could be accepted as a good tradition for Indonesian Muslim communities because they preserve good local traditions, and not violating fundamental principles in the doctrine of Islamic teachings. The research suggested the need to analyze local traditions with a broad religious perspective, preventing negative justifications and perversion.